Reviewing proposals for a world environmental organization - Lodefalk, Magnus (2002)
Examines the objectives and tasks of a world environmental organization (WEO). Makes suggestions as to how to organise a WEO, and how to deal with the budget, funding and membership. Focuses on principles/rules for a WEO.